2001
DOI: 10.1183/09031936.01.17509090
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust enhances airway responsiveness in asthmatic subjects

Abstract: Particulate matter (PM) pollution has been associated with negative health effects, including exacerbations of asthma following exposure to PM peaks. The aim of the present study was to investigate the effects of short-term exposure to diesel exhaust (DE) in asthmatics, by specifically addressing the effects on airway hyperresponsiveness, lung function and airway inflammation.Fourteen nonsmoking, atopic asthmatics with stable disease, on continuous treatment with inhaled corticosteroids, were included. All wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
3
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(118 citation statements)
references
References 35 publications
8
103
3
4
Order By: Relevance
“…Most studies generally did not found effects on lung function parameters in relation to short-term air pollution chamber exposure [9][10][11][12][13][14]. Compared with the chamber studies, our study explored the pulmonary effects in the natural environment, where more complex traffic-related air pollutants existed, this may lead to the discrepancies between the findings of the chamber studies and our own.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Most studies generally did not found effects on lung function parameters in relation to short-term air pollution chamber exposure [9][10][11][12][13][14]. Compared with the chamber studies, our study explored the pulmonary effects in the natural environment, where more complex traffic-related air pollutants existed, this may lead to the discrepancies between the findings of the chamber studies and our own.…”
Section: Discussioncontrasting
confidence: 48%
“…Acute respiratory effects of exposure to diesel exhaust have also been studied in controlled chamber studies [9][10][11][12][13][14][15]. Most studies generally did not found effects on lung function parameters in relation to short-term air pollution chamber exposure [9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it is capable of inducing AHR in naïve mice in the absence of allergen [62,108]. It has also been demonstrated that DEP alone can induce increased AHR in asthmatic individuals [109]. While these effects may be related to PM effects on the immune system, the particles and their components may directly contribute to increased AHR during asthma attack [110][111][112].…”
Section: The Impact Of Particulate Pollutants On Asthmamentioning
confidence: 99%
“…(2010), whole body plethysmography is “a rather crude indicator of pulmonary function”, and as they did not use confirmatory methods of lung function assessment based on physical principles, their “pulmonary responsiveness” data should be viewed with some caution 32 . In saying this, it is well established that influenza infection results in pulmonary hyper‐reactivity in mice 24 and humans, 33 and that diesel exposure causes airway hyper‐reactivity in humans 34 . Interestingly, Gowdy et al.…”
Section: Introductionmentioning
confidence: 99%